Identification of angiotensin I-converting enzyme inhibitory peptides from enzymatic hydrolysates of pork loin. Issue 1 (1st January 2019) - Choe, Juhui; Seol, Kuk-Hwan; Son, Dong-In; Lee, Hyun Jung; Lee, Mooha; Jo, Cheorun
ABSTRACT: This study aimed to identify angiotensin I-converting enzyme (ACE) inhibitory peptides in enzymatic hydrolysates from pork loin. Pork hydrolysates were produced by injecting different enzymes to the loins as follows: un-injected pork (fresh pork), injected with water (no enzyme control), 100 ppm protease type XIII (E1), 80 ppm thermolysin (E2), and the combination of 100 ppm protease type XIII and 80 ppm thermolysin (E3). The highest degree of hydrolysis (96.7%) and ACE inhibitory activity (90.1%) were observed in the E2-treated hydrolysate. Next, the E2-treated hydrolysate was fractionated and purified by using two different chromatographic methods, and the fractions with the highest ACE inhibitory activity were selected at each step. Finally, two peptides (Leu-Val-Gly-Arg-Pro-Arg-His-Gly-Gln and Val-Phe-Pro-Ser) were identified in the E2-treated hydrolysate using UPLC-QTOF-MS/MS. The smaller peptide, Val-Phe-Pro-Ser, showed a lower IC50 value for ACE inhibitory activity than the nona-peptide and captopril, a commercial ACE inhibitor. The results of this study suggest that the isolated nona-peptide, Leu-Val-Gly-Arg-Pro-Arg-His-Gly-Gln, possessed strong ACE inhibitory activity. Therefore, overnight incubation of fresh pork in a refrigerator after thermolysin injection may make the pork more beneficial for human consumption. Graphical Abstract: